2014
DOI: 10.1103/physreva.90.033803
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous locking of optical vortices in coupled semiconductor lasers

Abstract: Non-conventional emission of light, comprising engaged rotating light cogs, is measured and analyzed. The source of this unique emission is an array of coupled surface emitting lasers, each emitting an optical vortex. The complex rotating light structures are formed spontaneously by specific combinations of the individual vortices, each carrying two types of "charge": orbital angular momentum (±1 topological charge) and a relative engagement phase (0 or π ). These charges determine the specific form in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…We experimentally detected and calculated the near-field and far-field intensity distributions of the first and second harmonics outputs when phase locking an array of even number (10) and odd number (11) of lasers arranged on a ring geometry. For the calculations, we assumed that the laser output intensities are equal, have Gaussian profiles, and out-of-phase or in-phase distributions when the lasers are phase locked.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We experimentally detected and calculated the near-field and far-field intensity distributions of the first and second harmonics outputs when phase locking an array of even number (10) and odd number (11) of lasers arranged on a ring geometry. For the calculations, we assumed that the laser output intensities are equal, have Gaussian profiles, and out-of-phase or in-phase distributions when the lasers are phase locked.…”
Section: Resultsmentioning
confidence: 99%
“…In related investigations, it was found that waveguide arrays behave as photonic topological insulators in certain geometries [10]. Recently, a difference between the emission patterns from even and odd number of coupled vertical cavity surface emitting lasers (VCSELs) in a circular geometry was noted in a scenario in which the emission from each VCSEL is a single optical vortex with a unit topological charge [11].…”
Section: Introductionmentioning
confidence: 99%
“…By analogy with the quasi-scalar case [28-32, 39, 40] one might anticipate also the possibility of stabilization of vector vortices in the flow-equilibrium of driven dissipative systems like cavities. VCSELs are attractive for this kind of studies as they allow a huge variety of spatial [41][42][43][44][45] as well as polarization [41,44,[46][47][48][49][50] states due to their high Fresnel number and nominal circular symmetry. Theoretically, vector vortex beams were predicted for VCSEL modes in [51], but never experimentally observed.…”
mentioning
confidence: 99%